An analysis of nanosecond-pulsed streamer discharges in treating melanoma cells: generation, source–plasma interaction, and energy efficiency - Elaissi, Samira; Alsaif, Norah A. M.; Moneer, Eman M.; Gouadria, Soumaya (Frontiers in Physics, 2025)
Atmospheric pressure plasma has great potential in medicine, such as cancer therapy and wound treatment. Skin cancer therapy is challenging due to the thin layer of biological liquid covering the sample. This study aims to perform a numerical simulation of nanosecond high-voltage pulse plasma streamers applied to human tissue for melanoma cell therapy. This study investigates the optimization of plasma energy transfer in relation to several parameters, such as voltage, total energy, pulse frequency, flow rate, input power, and pressure. Results show that transient electric discharges can reach much higher electron energy levels than static discharges. As voltage increases, most reactive species’ densities increase, and streamer length increases due to higher power deposition. In addition, as the pressure varies from 1 atm to 0.3 MPa, the breakdown time increases, and the propagation velocity of the ionizing front decreases. Pulse frequency affects thermal processes because contact time and input power of plasma increase with frequency. Due to a gradual cascade of biochemical processes that occur after treatment, melanoma cells often undergo apoptosis, resulting in slow cell death rather than necrosis, which occurs immediately. Melanoma cell death is most likely caused by the hydroxyl radical OH species produced from water vapor, which damages the outer surface of cancer cells through the oxidation process. Reactive oxygen and nitrogen species (RONS) like NO and O arising as primary products or metabolic byproducts have less influence. Based on these findings, it appears that these results are extremely important for treating cancer cells with non-thermal streamer discharge plasma.